Distortions to agricultural incentives along value chains - Tokgoz, Simla (International Food Policy Research Institute, 2018)
Development of agricultural value chains is necessary to help smallholder farmers in Africa. Domestic agricultural policies and trade policies impact all economic agents along the value chain, from farmers to traders to consumers. Thus, it is critical to understand the impact of policy distortions to agricultural incentives along the complete value chain. This AGRODEP Technical Note provides a description of the Nominal Rate of Protection methodology that can be utilized to analyze agricultural policies in a value chain context. It also provides a description of the Incentives along Value Chains (IVC) Toolbox in Excel, developed to aid AGRODEP researchers in conducting this type of analysis with a focus on agriculture.